TRADITIONAL TITLES AND POLITICAL COMMUNICATION IN GORONTALO - Sumarjo; Bajari, Atwar (Jurnal Kaganga: Jurnal Ilmiah Sosial dan Humaniora, 2021)
Each region has its own peculiarities that refers to the culture of its people. In this diverse culture, there are customs that are maintained as continuous, preserved and practiced in social life. The aims of the research are: (a) to reveal the meaning of adat title in local political communication, (b) to know the meaning of political communication capital in local government in Gorontalo, and (c) to get the pattern of political communication capital in local government in Gorontalo. The research doing by the critical ethnography, which is focus on the discovery, interpretation, and application of local knowledge to practice, rather than on testing hypotheses or outcomes. As a customary area, Gorontalo has a tradition of giving traditional titles (Pulanga)to the local son who is considered to have a great contribution to the region. The awarding of traditional titles/returns as a form of homage to new officials to distinguish them from others in society. The preservation of the traditions of the awarding ceremony is a sign that custom exists in Gorontalo society. So far, the awards have not clashed with democracy, although in certain aspects such as the recognition of women's leadership, not yet fully compatible with democracy. This paper examines how customary / traditional titles can be used as political capital in a contestation in Gorontalo for political office positions.Key words: gelaradat, modal politik, Gorontalo.